String Photini at the LHC - Arvanitaki, A; Craig, N; Dimopoulos, S; Dubovsky, S; March-Russell, J (2009)
String theories with topologically complex compactification manifolds suggest the simultaneous presence of many unbroken U(1)'s without any light matter charged under them. The gauge bosons associated with these U(1)'s do not have direct observational consequences. However, in the presence of low energy supersymmetry the gauge fermions associated with these U(1)'s, the "photini", mix with the Bino and extend the MSSM neutralino sector. This leads to novel signatures at the LHC. The lightest ordinary supersymmetric particle (LOSP) can decay to any one of these photini. In turn, photini may transition into each other, leading to high lepton and jet multiplicities. Both the LOSP decays and inter-photini transitions can lead to displaced vertices. When the interphotini decays happen outside the detector, the cascades can result in different photini escaping the detector leading to multiple reconstructed masses for the invisible particle. If the LOSP is charged, it stops in the detector and decays out-of-time to photini, with the possibility that the produced final photini vary from event to event. Observation of a plenitude of photini at the LHC would be evidence that we live in a string vacuum with a topologically rich compactification manifold.